2019
DOI: 10.3390/genes10050390
|View full text |Cite
|
Sign up to set email alerts
|

Functional Characterization of Date Palm Aquaporin Gene PdPIP1;2 Confers Drought and Salinity Tolerance to Yeast and Arabidopsis

Abstract: Recent studies on salinity tolerance in date palm revealed the discovery of salt-responsive genes including PdPIP1;2, a highly conserved aquaporin gene in plants, which was functionally characterized in this study to investigate its precise role in drought and salinity tolerance. Immunoblot assay showed a high level of PIP1 protein accumulation only in the leaves of date palm plants when grown under drought, an observation which may imply the involvement of PIP1;2 in CO2 uptake. Heterologous overexpression of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 53 publications
1
29
0
Order By: Relevance
“…The AQP family in these three species has been systematically characterized, providing valuable information for further functional analysis to infer the roles of AQPs in adaptation to diverse environmental conditions [ 45 , 47 , 48 ]. Psammophytes jojoba ( Simmondsia chinensis ), date palm ( Phoenix dactylifera ), and jujube ( Ziziphus jujuba ) can all tolerate drought, salinity, and nutrient stress, and their AQP genes have been intensively studied to better understand their potential for genetic engineering to improve plant stress tolerance [ 39 , 49 , 50 ]. The halophytes Atriplex canescens , Sesuvium portulacastrum , and Thellungiella salsuginea all exhibit strong salt tolerance, and their PIP genes have been found to function in the response to salt stress and could be used in genetic engineering to improve plant growth under abiotic stress [ 33 , 35 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The AQP family in these three species has been systematically characterized, providing valuable information for further functional analysis to infer the roles of AQPs in adaptation to diverse environmental conditions [ 45 , 47 , 48 ]. Psammophytes jojoba ( Simmondsia chinensis ), date palm ( Phoenix dactylifera ), and jujube ( Ziziphus jujuba ) can all tolerate drought, salinity, and nutrient stress, and their AQP genes have been intensively studied to better understand their potential for genetic engineering to improve plant stress tolerance [ 39 , 49 , 50 ]. The halophytes Atriplex canescens , Sesuvium portulacastrum , and Thellungiella salsuginea all exhibit strong salt tolerance, and their PIP genes have been found to function in the response to salt stress and could be used in genetic engineering to improve plant growth under abiotic stress [ 33 , 35 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a unicellular eukaryote with a rapid growth rate, yeast has become a convenient protein expression system for protein functional identification. We found that inducing the expression of CrPIP2;3 in yeast ( Figure S4A ) resulted in obvious sensitivity to high salt and high osmotic stress ( Figure 4 ), which is, to some extent, opposite to that observed in other plant PIP members, such as barley PIP2;5 ( HvPIP2;5 ), foxtail millet SiPIP3;1 and SiSIP1;1 , and date palm PdPIP1;2 , which improved salt and osmotic stress tolerance in yeast [ 49 , 52 , 53 ]. Similarly, mammalian AQP1 and AQP5 caused moderate growth inhibition under salt and hyperosmotic stress when expressed in yeast [ 54 ], and many AQPs have been confirmed as membrane transporters of H 2 O 2 in the plant response to stress [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies on the response of date palm to abiotic stresses are limited and the explicit mechanisms of stress tolerance are yet to be identified. The transcriptome, methylome and miRNAome of salinity-stressed date palm offer some insights into the complex abiotic stress tolerance mechanisms [12,13,14,15,16,17]. Specifically, the global gene expression profiles of salt-stressed date palm have identified a differentially expressed genetic makeup [12].…”
Section: Introductionmentioning
confidence: 99%
“…In a related study, Patankar et al (2019b) expressed date palm aquaporin PdPIP1;2 in yeast and reported improved tolerance to salinity and oxidative stresses. On the other hand, overexpression of the same gene in Arabidopsis showed symptoms of improved tolerance including enhanced biomass, chlorophyll content, root length under salt and drought conditions and high K + /Na + compared to wild type.…”
Section: Salinity Salinity Tolerance In Date Palmsmentioning
confidence: 99%